HIDROGEOLOGI AIR TANAH: STUDI KASUS PADA LUBANG BUKAAN BEKAS PENAMBANGAN BIJIH MANGAN DI DUSUN KLIRIPAN KABUPATEN KULONPROGO - Suyono; Halimah Tusak Diah; Tedy Agung Cahyadi (INTAN Jurnal Penelitian Tambang, 2020)
The study was conducted in the opening hole of the former manganese ore mining of Vertical Shaft (PTPM) and Inclined Shaft (Sunoto) located in Dusun Kliripan, Desa Hargorejo, Kecamatan Kokap, Kabupaten Kulonprogo, Provinsi Daerah Istimewa Yogyakarta. The two planned openings will be the object of geological tourism and underground mining practice of mining engineering students. This research wants to study the hydrogeological conditions in the Dusun Kliripan. The methods used in this research are literature study, field orientation, primary data collection including measurement of groundwater level and infiltration rate, as well as the topography of the study area, secondary data include rainfall data, topographic maps, and geological maps, and hydrogeological maps. The next stage includes data processing, as well as the study of data processing results. The results obtained were lithology conditions including Frozen Rock, Volcanic Breccia, and Limestone, the average infiltration rate obtained was 0.16 cm/min, the groundwater level in the Kliripan was at an elevation of 70 masl to 92 masl, with basin groundwater is included in the Menoreh Groundwater Basin area. The Kliripan area has a sufficiently good groundwater reserve with complete hydrogeological elements so that it can be used for continued use of groundwater in the region.